2020
DOI: 10.1038/s41467-020-17139-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pharmaco-proteogenomics defines two subgroups in isocitrate dehydrogenase wild-type glioblastoma with prognostic and therapeutic opportunities

Abstract: The prognostic and therapeutic relevance of molecular subtypes for the most aggressive isocitrate dehydrogenase 1/2 (IDH) wild-type glioblastoma (GBM) is currently limited due to high molecular heterogeneity of the tumors that impedes patient stratification. Here, we describe a distinct binary classification of IDH wild-type GBM tumors derived from a quantitative proteomic analysis of 39 IDH wild-type GBMs as well as IDH mutant and low-grade glioma controls. Specifically, GBM proteomic cluster 1 (GPC1) tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…The appeal of radiomics and radiogenomics in the care of patients with high-grade gliomas is obvious when one considers the primary diagnostic dilemmas faced in the neuro-oncology clinic, which begin the moment a patient presents to medical attention and continue through each line of treatment. Due to the marked interpatient heterogeneity of the disease in terms of both underlying tumor biology and clinical outcomes [ 4 , 17 , 18 ], one of the earliest challenges in the care of a patient with glioma is predicting the aggressiveness of that individual’s tumor and, therefore, the expected time to tumor recurrence and death. For the nearly 90% of patients with high-grade glioma who do not participate in a first-line clinical trial [ 19 ], temozolomide-based chemoradiotherapy is administered routinely despite great uncertainty around the degree of benefit that any one individual will gain from it.…”
Section: Can Radiomics Aid In Clinical Decision-making? a Neuro-oncology Perspectivementioning
confidence: 99%
“…The appeal of radiomics and radiogenomics in the care of patients with high-grade gliomas is obvious when one considers the primary diagnostic dilemmas faced in the neuro-oncology clinic, which begin the moment a patient presents to medical attention and continue through each line of treatment. Due to the marked interpatient heterogeneity of the disease in terms of both underlying tumor biology and clinical outcomes [ 4 , 17 , 18 ], one of the earliest challenges in the care of a patient with glioma is predicting the aggressiveness of that individual’s tumor and, therefore, the expected time to tumor recurrence and death. For the nearly 90% of patients with high-grade glioma who do not participate in a first-line clinical trial [ 19 ], temozolomide-based chemoradiotherapy is administered routinely despite great uncertainty around the degree of benefit that any one individual will gain from it.…”
Section: Can Radiomics Aid In Clinical Decision-making? a Neuro-oncology Perspectivementioning
confidence: 99%
“…In 2010, four subtypes of GBM (proneural, neural, classic, and mesenchymal) have been categorized based on the transcriptomic analysis; however, it was shown to be less homogenous than the genomic one ( Verhaak et al, 2010 ; Wang et al, 2017 ). More recently, integrated pharmaco-proteogenomic studies were performed on GBM resulting in two subgroups within the IDH wild-type group showing different prognostic and therapeutic opportunities ( Oh et al, 2020 ). Moreover, the integrative analysis of the protein profile, the RNA expression, and the patient clinical information enable the identification of specific signaling pathways related to immune, metabolic, and developmental processes and associated with a patient survival ( Yanovich-Arad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…TP53 mutation is one of the most common alterations across tumor types [ 22 ], and is observed in the early stages of GBM, along with changes in related pathways [ 17 , 67 , 68 ]. However, its association with GBM TS isolation rate was not reported yet [ 1 , 41 , 44 , 47 , 69 71 ]. In this retrospective analysis, we found that TP53 mutants were more amenable to isolation from tissue (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%